Understanding what Business Marketing Strategy will Continue in 2022: Business Literacy Prediction Study - Chadhiq, Umar; Suslinawati, Suslinawati; Dyanasari, Dyanasari; Fachrurazi, Fachrurazi; Nurcholifah, Ita (Budapest International Research and Critics University, 2022)
One of the essential elements of a successful business is a marketing strategy. This study aims to obtain evidence that field studies of business marketing strategies in 2002 will continue. To answer this question, we have successfully obtained a series of data and information searches electronically on several publication databases in academic scientific publications, books, and media websites that discuss marketing issues and predictions in 2022. These data are meaningless to this research without a review. An in-depth study involves a data coding system for interpreting digest data to answer the questions of this study. We focus on this literature search for publications between 2010 and 2022, considering that this period was one of the most intense periods of technological and information changes related to how businesses responded to these developments to promote their business. With the results of the study and discussion of the data findings, we can finally conclude that the understanding of business marketing strategies that will continue in 2022 is the use of the latest technological means, including artificial intelligence social media, and a number of the latest applications where it is proven that the application data is very relevant for marketing all products and services.